Dissociation of Escherichia coli heat-labile enterotoxin adjuvanticity from ADP-ribosyltransferase activity. - Dickinson, B L (1995)
The heat-labile enterotoxin (LT) of Escherichia coli is immunologically and physiochemically related to cholera enterotoxin. A number of studies have been performed to determine the relationship of the ADP-ribosylating enzymatic activity of these enterotoxins to toxicity and adjuvanticity. These studies have generally examined the effect of abolishing the ADP-ribosyltransferase activity of A1 by a variety of chemical or genetic manipulations. In every case, loss of enzymatic activity was associated with loss of biological activity and also with the ability of the molecules to function as oral adjuvants. Consequently, we explored an alternate approach to detoxification of LT without altering its adjuvanticity. Specifically, we generated a novel mutant form of LT by genetic modification of the proteolytically sensitive residues that join the A1 and A2 components of the A subunit. This mutant contains a single amino acid substitution within the disulfide subtended region joining A1 and A2. This mutant toxin, designated LT(R192G), is not sensitive to proteolytic activation, has negligible activity on mouse Y-1 adrenal tumor cells, and is devoid of ADP-ribosyltransferase activity. Nonetheless, LT(R192G) retains the ability to function as a mucosal adjuvant, increasing the serum immunoglobulin G (IgG) and mucosal IgA responses to coadministered antigen (OVA) beyond that achieved with administration of that antigen alone. Further, LT(R192G) prevented the induction of tolerance to coadministered antigen and did not induce tolerance against itself, as demonstrated by the presence of significant serum anti-LT IgG and mucosal anti-LT IgA antibodies in immunized mice.